Outdoor Motivational Training and Discussion to Improve Adolescents’ Knowledge and Attitudes towards Smoking - Ika Fidianingsih (Journal of Educational, Health and Community Psychology, 2020)
AbstractThe prevalence of smoking among adolescents is relatively high and continues to increase. Providing information or knowledge about the dangers of smoking and encouragement to quit smoking is necessary. Discussion and outbound methods are expected to improve knowledge and attitudes towards smoking. This study aimed to identify the improvement in knowledge and attitudes towards smoking following discussion and outbound activities. This was a quasi-experimental study with a total of 30 subjects aged 12-25 years old recruited using the consecutive method. Subjects were requested to complete a pre-test and post-test about their knowledge of smoking as well as an attitude questionnaire after participating in a discussion and outbound (outdoor motivational training). The paired T-test or Wilcoxon test was employed in the statistical analysis (95% confidence level, α = 0.05). A total of 11 adolescents were smokers (36.7%). The knowledge pre-test and post-test scores were 70.83±13.47 and 75.21±16.37 (p=0.063), while those for attitudes were 77.73±11.26 and 78.4±10.35 (p=0.674), respectively. To conclude, there was no improvement in the knowledge or attitudes towards smoking after the knowledge transferred through discussion and outbound.Keywords: Outdoor motivational training, smoking, discussion, knowledge, attitudes